1998
DOI: 10.3168/jds.s0022-0302(98)75752-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulation of Murine Spleen Cells by Materials Associated with Bovine Milk Protein Fractions

Abstract: Purified bovine milk proteins that were added to cultures of murine spleen cells significantly increased cell proliferation and production of immunoglobulin M. Casein and a whey mixture consisting of alpha-lactalbumin, bovine serum albumin, bovine gamma globulin, and beta-lactoglobulin (beta-LG) were stimulatory. Of the three beta-LG preparations that are commercially available (beta-LG containing variants A and B, purified variant A, and purified variant B), the unseparated mixture containing both the A and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 19 publications
5
37
3
Order By: Relevance
“…Mahmud, Matn, and Otani (2004) also found that purified b-LG induces proliferation of mouse resting spleen cells and that mitogenic activity is retained following reduction of the protein, suggesting that the activity depends on the primary structure. However, in contrast to the previous study (Wong et al, 1998), they reported that the mitogenic activity of b-LG is stronger following a 3 h digestion with pepsin, trypsin, chymotrypsin or pancreatin, supporting the view that peptides may be responsible for this activity. In addition, they showed that the most mitogenic pancreatic H induces significant growth of a human B cell line (U266), but does not influence the growth of other cell lines (Ball human B cells, MOLT-4 and Jurkat T cells).…”
Section: Lymphocyte Activation and Proliferationmentioning
confidence: 47%
“…Mahmud, Matn, and Otani (2004) also found that purified b-LG induces proliferation of mouse resting spleen cells and that mitogenic activity is retained following reduction of the protein, suggesting that the activity depends on the primary structure. However, in contrast to the previous study (Wong et al, 1998), they reported that the mitogenic activity of b-LG is stronger following a 3 h digestion with pepsin, trypsin, chymotrypsin or pancreatin, supporting the view that peptides may be responsible for this activity. In addition, they showed that the most mitogenic pancreatic H induces significant growth of a human B cell line (U266), but does not influence the growth of other cell lines (Ball human B cells, MOLT-4 and Jurkat T cells).…”
Section: Lymphocyte Activation and Proliferationmentioning
confidence: 47%
“…Several in vitro studies involving murine material have demonstrated immunomodulatory effects of bovine WP preparations on splenic lymphocyte clonal expansion and function. Wong et al (1998) provided evidence that a WP mixture can significantly increase cell expansion and production of IgM by splenocytes. Mercier et al (2004) found whey protein from isolates to significantly induce proliferation of splenic lymphocytes without mitogen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-globulins have been suggested to be activators of PMN functions [33] and their pattern could be related to the RB pattern observed [23].…”
Section: Discussionmentioning
confidence: 99%